Exploring Relationships between Role Conflict and Ambiguity with Administrator’s Overload and Burnout in Public University of China - Li, Xiaotian; Ye, Yan (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
School administrative staffs often have multiple roles, a phenomenon that leads to role conflict, ambiguity, burnout, and overload. More and more attention has been paid to these problems of school administrative staffs’ mental health. This study used mixed methods research to examine the perception of 147 full-time school administrative staffs in a public university in Shanxi province, China. For the qualitative method, the researcher interviewed five administrative staffs in the university to collect information, and for the quantitative method, the author adopted three sets of questionnaires, Administrative staff Stress Index, Maslach Burnout Inventory, and Role conflict and ambiguity. From the preliminary interview, the administrative staffs in different departments reflected they were under work overload and burnout, with role conflict and ambiguity. The results of quantitative data showed that in the university, the administrative staff’s role conflict and ambiguity were significant with overload (r = .314 Sig. 2-tailed was. 000), and there was a significant relationship between role conflict and ambiguity with burnout (r = .649 Sig. 2-tailed was. 000). Of these, administrative overload was greatest in the administrative constraint and responsibility areas. In terms of burnout, emotional exhaustion and depersonalization are often places where stress is concentrated and the main cause of it. Measures to solve administrative staff’s burnout and overload problems are provided in this article’s discussion section.